Comparison between Flow Cytometry and Traditional Culture Methods for Efficacy Assessment of Six Disinfectant Agents against Nosocomial Bacterial Species - Massicotte, Richard; Mafu, Akier A.; Ahmad, Darakhshan; Deshaies, Francis; Pichette, Gilbert; Belhumeur, Pierre (Frontiers in Microbiology, 2017)
The present study was undertaken to compare the use of flow cytometry (FCM) with the standard culture-based microbiology method to assess the efficacy of six disinfectants used in Quebec hospitals including: two quaternary ammonium-based, two activated hydrogen peroxide-based, one phenol-based and one sodium hypochlorite-based. Four nosocomial bacterial species, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Vancomycin-resistant Enterococci faecalis, were exposed to minimum lethal concentrations (MLCs) and sublethal concentrations (1/2 MLCs) of disinfectants under study. The results showed a strong correlation between the two techniques for the presence of dead and live cell populations, as well as, evidence of injured populations with the FCM. The only exception was observed with sodium hypochlorite at higher concentrations where fluorescence was diminished and underestimating dead cell population. The results also showed that FCM can replace traditional microbiological methods to study disinfectant efficacy on bacteria. Furthermore, FCM profiles for E. coli and E. faecalis cells exposed to sublethal concentrations exhibited distinct populations of injured cells, opening a new aspect for future research and investigation to elucidate the role of injured, culturable/noncuturable/resuscitable cell populations in infection control.